2006
DOI: 10.1194/jlr.m600061-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A combined with retinoic acid increases retinol uptake and lung retinyl ester formation in a synergistic manner in neonatal rats

Abstract: Vitamin A (VA) is stored in tissues predominantly as retinyl esters (REs), which provide substrate for the production of bioactive retinoids. Retinoic acid (RA), a principal metabolite, has been shown to induce postnatal lung development. To better understand lung RE storage, we compared VA (given as retinyl palmitate), RA, and a nutrient-metabolite combination, VARA, given orally on postnatal days 5-7, for their ability to increase lung RE in neonatal rats. VARA increased lung RE significantly [z14, 2.4, 2.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 48 publications
7
86
1
3
Order By: Relevance
“…This observation was similar to findings in neonatal piglets, in which the liver ranked as the highest in terms of retinol concentration, followed by the kidneys and lungs, irrespective of VA treatment (23). However, kinetic studies in rats supplemented with VARA have shown a dramatic stimulatory effect of supplementation on the uptake and retention of retinyl esters by the lungs and intestine (14,36), consistent with the previously demonstrated role of retinoic acid in upregulating genes responsible for VA storage (37)(38)(39). Based on these results, we speculate that VA alone may not be as effective as VARA in promoting extrahepatic retinol deposition, although future kinetic analyses of our data are needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…This observation was similar to findings in neonatal piglets, in which the liver ranked as the highest in terms of retinol concentration, followed by the kidneys and lungs, irrespective of VA treatment (23). However, kinetic studies in rats supplemented with VARA have shown a dramatic stimulatory effect of supplementation on the uptake and retention of retinyl esters by the lungs and intestine (14,36), consistent with the previously demonstrated role of retinoic acid in upregulating genes responsible for VA storage (37)(38)(39). Based on these results, we speculate that VA alone may not be as effective as VARA in promoting extrahepatic retinol deposition, although future kinetic analyses of our data are needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…In experiment 1 (3 day study, n = 4/group) 5 day old neonates were treated once a day for 3 days with oil (control), VA alone, RA, 9-cis -RA, both isomers mixed in a 1:1 ratio, or VA combined with each the same acidic retinoids. Twenty-four hours after the last treatment, neonates were euthanized and tissues collected ( 12 ). In experiments 2 and 3 (acute studies lasting 6 and 12 h), 6-7 day old pups were treated with oil (control), VA alone, RA alone, Am580 alone, VA combined with RA (VARA), or with Am580 (VAAm).…”
Section: Animals and Experimental Designsmentioning
confidence: 99%
“…As RA is not reduced to retinol in vivo and thus is not a substrate for tissue RE synthesis, the increase in RE in the lungs implies that RA plays a regulatory role in this organ, in some manner facilitating RE formation. The synergistic effect of VARA was selective for the lungs, as RE formation in the liver did not differ between VARA and an equal dose of VA only ( 12,17 ). In a metabolic study using [ 3 H]retinol to trace the uptake of newly absorbed retinol, we found that RA served to direct more of the [ 3 H]retinol tracer and, thus, the oral VA supplement, into the neonatal lung ( 12 ).…”
mentioning
confidence: 99%
“…The administration of ATRA to pregnant rats results in the rapid transfer across the placenta to the fetuses (27). Lung retinyl ester was increased in neonatal rats treated with ATRA and retinyl ester storage granules were increased by exogenous ATRA in cultured lipid interstitial cells (28,29). RA exerts its effects through nuclear retinoic acid receptors, which are present in the fetal rat lung (30).…”
Section: Discussionmentioning
confidence: 99%